MELAWAN MITOS PARADIGMA PEMBANGUNAN BERKELANJUTAN DENGAN PENDEKATAN LINGKUNGAN PROFETIK - Fathoni Fathoni (Postgraduate State Islamic Institute (IAIN) Metro, 2016)
Globalization with its liberalism-capitalistic concept promotes us about materialism that everything has to count as matter. Including how is their perspective about the relation between the human and environment. It is inevitable that environment just as object to emerge the benefit for human being and their life. This paradigm emerges the concept of sustainable development to emphasize and strengthen the link between the conservation of natural ecosystems and human development. The concept of sustainable development as such has been on the scene since at least 1987 when the World Commission on Environment and Development published the Brundtland Report. The substance of